Enhancing the effectiveness of minimum employment standards in New Zealand. (September 2019) - Anderson, Gordon; Kenner, Lucy
Employer breaches of New Zealand's minimum employer standards and other forms of worker exploitation have been increasingly recognised as a significant problem. This affects migrant workers in particular, and among them those working without documentation or on various types of non-resident visas. Exploitation has become particularly embedded in a number of industries: fishing, hospitality and tourism, and in some sectors of agriculture, particularly those dependent on seasonal labour. Initially, government action to mitigate these problems was slow and reluctant but over the last decade, culminating in the reforms of 2016, there has been a more focussed effort to provide a strong legislative framework to support minimum employment standards. This article describes the background to those reforms, analyses the reforms themselves and goes on to consider whether they are adequate to ensure access to justice by disadvantaged workers. JEL Codes: J81, J83, J88